The effect of a home visitation program on mother–infant interactions - Başar, Zeynep. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2020., 2020)
A large body of research reveals that warm, responsive, and stimulating parent-child interactions contribute in many ways to infants’ emerging socio-emotional, cognitive, and language competencies and attachment relationship. However, caregivers are less likely to engage in developmentally supportive practices in high risk families. Thus, home visiting programs that target low-income families aim to strengthen the quality of caregiver-child relationship and positive parenting practices, improve maternal health and reduce child abuse as well as neglect. These improvements in return, are expected to contribute to infants’ socio-emotional, cognitive, and physical development. The primary aim of this study is to assess the impact of a home visitation program on infants’ development and on mothers’ parenting practices, who received biweekly home visits from the prenatal period throughout the first 18 months of their infants’ life. Target outcomes were assessed with direct behavioral observations of mother-infant-dyads in a research laboratory during a free play and a structured teaching task context. Lastly, this study also aims to explore whether different subgroups of mothers, such as highly depressed mothers, were affected differently by the program. Results of this study revealed that home-visited infants had higher language scores and home-visited mothers had higher respect for autonomy compared to the control group. Also, subgroup analysis demonstrated that the intervention improved the sensitivity, pointing, verbal responsiveness, and stimulation of highly depressed mothers. Implications were made based on those outcomes.
Keywords: Mother and infant.; Social interaction in infants.; Infant psychology.